2007
DOI: 10.1007/s10620-007-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Efficacy and Safety of Continuous Intravenous Infusion of Pantoprazole in the Treatment of Severe Erosive Esophagitis

Abstract: Severe erosive esophagitis can be completely healed in a few days if pantoprazole is given intravenously and continuously for 72 h. It is safe to give pantoprazole intravenously and continuously for treatment of severe erosive esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…PPIs only inhibit stimulated parietal cells with active proton pumps and this is most successfully and rapidly achieved by administering a bolus dose intravenously (providing 100% bioavailability theoretically); continuous infusion then provides a steady state of the drug to inactivate any newly synthesized proton pumps, as well as any newly recruited proton pumps on parietal cells which continue to be stimulated by gastrin, histamine and food [40]. In one study, oral and IV pantoprazole were equipotent in raising intra-gastric pH, when administered at the same dose and intervals [41].…”
Section: Intra-gastric Ph Studies-oral Versus Intravenous Ppimentioning
confidence: 99%
See 1 more Smart Citation
“…PPIs only inhibit stimulated parietal cells with active proton pumps and this is most successfully and rapidly achieved by administering a bolus dose intravenously (providing 100% bioavailability theoretically); continuous infusion then provides a steady state of the drug to inactivate any newly synthesized proton pumps, as well as any newly recruited proton pumps on parietal cells which continue to be stimulated by gastrin, histamine and food [40]. In one study, oral and IV pantoprazole were equipotent in raising intra-gastric pH, when administered at the same dose and intervals [41].…”
Section: Intra-gastric Ph Studies-oral Versus Intravenous Ppimentioning
confidence: 99%
“…The conventional dosage of infusional IVPPIs (80 mg bolus followed by 8 mg/h for 72 h), used in several studies and endorsed by consensus statements have been challenged by studies which have found no difference between high dosage and low dosage IVPPI [41,50,51]. Conducted a study across 11, Italian centers, and found no difference in in-hospital rebleeding and overall mortality rates, in patients who were given the conventional high dose PPI infusion, compared with those who had a standard dose of 40 mg IV daily for 72 h [52].…”
Section: Post-endoscopic Intravenous Ppimentioning
confidence: 99%
“…The decision to administer IV bolus PPI probably rests on a patient's ability to swallow oral PPIs. In a pilot study looking at the safety and efficacy of highdose infusional pantoprazole in the treatment of erosive esophagitis, patients with grade 4 esophagitis were randomized to receiving either high dose infusional or intermittent bolus IV pantoprazole (40 mg daily for 72 h) [Cai et al 2008]. Both groups were treated with oral pantoprazole 40 mg daily for 4 days afterwards.…”
Section: Intravenous Ppi In Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…Future targets for study include more extensive trials on the use of continuous iv pantoprazole in the treatment of severe erosive esophagitis and longterm studies on the safety and efficacy of oral suspension formulation. 58 In addition, expanding FDA approval for the use of pantoprazole in children and adolescents is currently being considered. 59,60…”
Section: Conclusion and Future Targetsmentioning
confidence: 99%